Métodos de manipulación en la medicina tradicional asiática. - Ramón Núñez, Hilda Marlene; Rodríguez, Gricel Benítez (MEDISAN, 2014)
Acupuncture, moxibustion and cups constitute methods of manipulation of the Asian traditional medicine which are frequently used, alone or combined, and they allow the prevention, treatment, as well as the cure of diseases. The review carried out is aimed at offering the professionals of the primary and secondary health levels a material for the study and updating of this topic.